Penerapan Teknologi Tepat Guna pada Bisnis Sosial sebagai Upaya Pencegahan Stunting di Desa Dersalam Kudus - Dina Lusianti; Keke Fahira; Vikha Asri (Penerbit Goodwood, 2026)
Purpose: This community service activity aims to empower women in Desa Dersalam, Kudus, by improving their skills in healthy food production and digital marketing as part of a social business that supports stunting prevention. The program is designed to help partners produce healthy food efficiently and promote their products through digital platforms. Methodology/Approach: The activity was conducted in Desa Dersalam and involved members of the Wanita Berdaya group. Several tools were used to support the training process, including an Air Fryer, Slow Juicer, and Chopper. The training was carried out through hands-on practice, demonstrations, mentoring, and social business workshops. Results/Findings: The program achieved several key outcomes. In digital marketing, ten participants actively promoted their products through social media, created at least three promotional contents each month, and successfully developed logos and brand identities ready for use. Conclusions: The use of appropriate technology has proven to improve efficiency, product quality, and hygiene in social business activities. Overall, this program supports community empowerment and makes a concrete contribution to stunting prevention efforts through increased knowledge, improved practices, and sustainable skill development. Limitations: The program faces a limitation in sustaining the mentoring phase, as some participants are not yet consistent in continuing production and digital marketing without intensive supervision. Contributions: Significant contributions include strengthening women’s capacity through appropriate technology and digital marketing, which supports family economic empowerment and community-based stunting prevention efforts in Dersalam, Kudus, Central Java.